2009
DOI: 10.1017/s1049023x00007408
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Preparedness of Post-Katrina and Rita Shelter Health Staff

Abstract: Introduction:During 2005, Hurricanes Katrina and Rita struck the US Gulf Coast, displacing approximately two million people. With >250,000 evacuees in shelters, volunteers from the American Red Cross (ARC) and other nongovernmental and faith-based organizations provided services. The objective of this study was to evaluate the composition, pre-deployment training, and recognition of scenarios with outbreak potential by shelter health staff.Methods:A rapid assessment using a 36-item questionnaire was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…[17][18][19][20] Similar to clients during Hurricane Katrina, many clients were referred to a higher level of care, including pharmacies, which suggests there are complex illnesses and needs seen in shelters, especially during mass care disasters. 17,18,21 For example, during this response, an evacuee from Louisiana with active tuberculosis was identified in triage (before entering a shelter) at a Mississippi shelter and was correctly referred to Louisiana public health for continuity of care. 22 Clearly, it is important that the Red Cross and other disaster response agencies (eg, Medical Reserve Corps) continue to roster qualified health services shelter personnel with triage and public health experience so that clients are properly assessed, treated, and referred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] Similar to clients during Hurricane Katrina, many clients were referred to a higher level of care, including pharmacies, which suggests there are complex illnesses and needs seen in shelters, especially during mass care disasters. 17,18,21 For example, during this response, an evacuee from Louisiana with active tuberculosis was identified in triage (before entering a shelter) at a Mississippi shelter and was correctly referred to Louisiana public health for continuity of care. 22 Clearly, it is important that the Red Cross and other disaster response agencies (eg, Medical Reserve Corps) continue to roster qualified health services shelter personnel with triage and public health experience so that clients are properly assessed, treated, and referred.…”
Section: Discussionmentioning
confidence: 99%
“…22 Clearly, it is important that the Red Cross and other disaster response agencies (eg, Medical Reserve Corps) continue to roster qualified health services shelter personnel with triage and public health experience so that clients are properly assessed, treated, and referred. 17,[21][22][23] The Red Cross is building its internal capacity to care for clients in its general population shelter through an increase in nursing practice scope and better integration of external health partners. An increase in shelter capacity to meet client health needs postdisaster would mean a decrease in surge on the community healthcare system, which is likely to be stressed after a disaster incident.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the qualitative studies combined interviews with observations (Broz et al 2009;Forrester et al 2014aForrester et al , 2014bNielsen et al 2015;Pathmanathan et al 2014;Summers et al 2014), with occasional studies adding focus groups (Carrion Martin et al 2016;Dynes et al 2015;Lee-Kwan et al 2014), documentary analysis (Abramowitz et al 2015;Krumkamp et al 2010) or community mapping (Hagan et al 2015). In the case of the mixed-methods studies, these either combined interviews with structured surveys (Bile et al 2010;Brahmbhatt et al 2010;Flores et al 2011), or interviews and observations with secondary data analysis (Brennan and Rimba 2005;Güereña-Burgueño et al 2006;Kilmarx et al 2014;Matanock et al 2014). Some mixed-methods studies also included focus groups (Atuyambe et al 2011) and case note reviews (Cheung et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…When considering the type of complex health emergency, we were able to divide the articles in two main categories: natural disasters with potential health consequences, and epidemic outbreaks (see Table 3). In the case of the articles on the health consequences of natural disasters, rapid research was used to: 1) assess the public health impact of the disaster (mainly on water and sanitation) (Atuyambe et al 2011;Brennan and Rimba 2005), 2) document existing infrastructure in order to plan humanitarian assistance (Bile et al 2010;Brahmbhatt et al 2010;Güereña-Burgueño et al 2006), or 3) evaluate the effectiveness of response strategies (Broz et al 2009).…”
Section: Complex Health Emergencies and Purpose Of The Researchmentioning
confidence: 99%
“…Public health considerations for sheltering and evacuation [56,57]: Studies identified in this theme describe the importance of the planning process to address the health needs of sheltered populations [57]. In addition, public health training in shelter operations was noted as a gap [56].…”
Section: Identification Of Themes Phasementioning
confidence: 99%